Breaking of the Up‐Down Symmetry of DNA Origami on a Solid Substrate - Velpula, Gangamallaiah; Tomm, Emilia; Shen, Boxuan; Mali, Kunal S.; Keller, Adrian Clemens; De Feyter, Steven (Angewandte Chemie International Edition)
Abstract Controlling the surface orientation of DNA origami nanostructures (DON) is crucial for applications in nanotechnology and materials science. While previous work utilized various DON modifications, simple methods for controlling their landing orientation remain scarce. Here, we demonstrate a straightforward approach to control the adsorption orientation of chiral double‐L (CDL) DON on mica by tuning magnesium ion (Mg 2 ⁺) concentration and exploiting global shape distortions. Using atomic force microscopy (AFM), we analyzed the resulting distribution of the mirror‐image orientations, referred to as S and Z orientations, at both buffer/mica and air/mica interfaces and identified conditions resulting in homogenous CDL orientation of 100% S. These results demonstrate how DON conformation and ionic environments influence DON orientation, offering insights for precise nanostructure deposition.